The Australian Aborigines and the Human Past - Partington, Geoffrey (The Australian journal of anthropology, 1985)
Indifference to events which may actually have taken place between the Dreamtime and European contact is commonly held to be a salient feature of traditional Aboriginal thought. This contention contains a significant element of truth but it may have been exaggerated by some anthropologists. Structural-functionalist emphases on myth as charter led not only to the rejection of historical interpretations of Aboriginal myths which were ill-considered and naïve, but also to an excessive neglect of potentially fruitful attempts to extract from myths clues about post-Dreamtime experiences. This neglect has unduly strengthened the view that Aboriginal thought is entirely sui generis and that its supposed indifference to human history is an inescapable cultural attribute of Aboriginality. A sketch is offered for a reappraisal of the significance of Aboriginal myths for Aboriginal history.